This preview shows page 1. Sign up to view the full content.
Unformatted text preview: f; that is, assume l (f) £-1 (f) = xHl + L k xHl-kyk + L k xl-kyk+l + yHl k=1 k=O = xHl + t. G)xHl-kyk + t. (k ~ 1)xHl-kyk + yHl = xHl + t. [ G) + (k ~ 1) ] xHl-kyk + yHl by identity (5) HI = '"" (f + 1) Hl-k k ~ k x y. k=O By the Principle of Mathematical Induction, the proof is complete. 19. (a) t, G) = G) + G) + G) + G) + (~) = 1 + 3 + 6 + 10 + 15 = 35 = G)' The sum here is the sum of the entries of Pascal's triangle on the third southwest-northeast diago-nal (f) beginning with the entry above and to the left of 35 = G) and moving up and right....
View Full Document
This note was uploaded on 11/08/2010 for the course MATH discrete m taught by Professor Any during the Summer '10 term at FSU.
- Summer '10
- Graph Theory